A revision of the species of Evaza Walker described by J.C.H. de Meijere (Diptera, Stratiomyidae, Pachygastrinae) - Rozkošný, Rudolf; Vaňhara, Jaromír (Zootaxa, 2017)
Six Oriental species of Evaza Walker, 1856 were described by J.C.H. de Meijere in the period between 1911 and 1924. The type specimens are now deposited in the Museum Naturalis (Leiden). All species were redescribed, photographed and their diagnostic characters were defined. Male terminalia of five species with known males were illustrated in detail. The revised species were compared with recently described new species from Oriental China. Additional material belonging to the revised species was recorded for the first time from the following countries: Evaza demeijerei Brunetti, 1923 (= E. pallipes de Meijere, 1916a) and E. discolor de Meijere, 1916a were found in Malaysia, E. javanensis de Meijere 1911 in Singapore, E. kerteszi de Meijere, 1914 in Laos and Malaysia and E. maculifera de Meijere, 1914 in Malaysia, Philippines, Thailand and Vietnam.